1989
DOI: 10.1021/jm00124a008
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, DNA-binding properties, and antitumor activity of novel distamycin derivatives

Abstract: A group of potential alkylating agents have been synthesized that are structurally related to the oligopeptide antiviral antibiotic distamycin. All derivatives form complexes with native calf-thymus DNA but compounds 2, 3, and 6 give rise to covalent adducts. Cytostatic activity against both human and murine tumor cell lines in vitro is displayed by the new compounds. Compounds 3 and 4 are active on melphalan-resistant L1210 leukemia in mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
81
0

Year Published

1991
1991
2010
2010

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(83 citation statements)
references
References 0 publications
2
81
0
Order By: Relevance
“…This was found both for DX, which intercalates into DNA (Arcamone et al, 1989), and for VP-16, which does not bind significantly to DNA. The reason for the loss of effect of the DNA topoisomerase II inhibitor is unclear.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…This was found both for DX, which intercalates into DNA (Arcamone et al, 1989), and for VP-16, which does not bind significantly to DNA. The reason for the loss of effect of the DNA topoisomerase II inhibitor is unclear.…”
Section: Discussionmentioning
confidence: 89%
“…To our knowledge, no reports have been published on the influence of polyamine levels on alkylating agents that bind in the DNA minor groove, such as tallimustine and CC-1065 (Hurley et al, 1988;Arcamone et al, 1989). These two drugs bind in the minor groove of AT-rich sequences and alkylate N3 adenine with a high degree of sequence specificity (Broggini et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…In the search for more ecacious and less toxic drugs, Zugmaier and colleagues (Zugmaier et al, 1992) found that the suramin-analogue heparinoid sodium-pentosan polysulphate (Figure 1), as well as other polyanionic sugars, was able to block the paracrine stimulant eects of GFs released from tumour cells including lung cancer. More recently, a series of polyanionic naphthalene sulphonate derivatives of distamycin A (Arcamone et al, 1989), have been synthesized (Biasoli et al, 1993). These compounds have a common skeleton of four methyl-pyrrolic rings on the naphthalene ring, but vary in the number and position of the SO 3 groups.…”
Section: Introductionmentioning
confidence: 99%
“…Summary Human colon adenocarcinoma cells (LoVo) (Arcamone et al, 1989;Kopka et al, 1985), is a novel antitumour compound currently being investigated in phase I clinical trials ( Figure 1). …”
mentioning
confidence: 99%